2006
DOI: 10.1590/s1516-89132006000600010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of betaine on the growth of the fish piauçu, Leporinus macrocephalus

Abstract: In this study was tested the effect of betaine on the growth performance of the piauçu fish. For this, twenty-one fish (mean ± SD: body weight: 14.9 ± 1.3 g) were randomly distributed in one out of three experimental treatments (n = 7 each; 1 fish/aquarium): without betaine added in the food (control); 3.6 g betaine/Kg of food; 7.1 g betaine/Kg of food. The fish were exposed to experimental conditions for 60 days. Fish presented significant growth throughout experimentation, but no statistically significant di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
7
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 19 publications
3
7
1
Order By: Relevance
“…have been reported in different fishes, indicating a species-specific betaine effect (Normandes et al, 2006). In this study, significantly higher FBW and SGR were observed in allogynogenetic gibel carp fed the diet containing 0.4% betaine than in the control group (p < .05).…”
supporting
confidence: 48%
See 2 more Smart Citations
“…have been reported in different fishes, indicating a species-specific betaine effect (Normandes et al, 2006). In this study, significantly higher FBW and SGR were observed in allogynogenetic gibel carp fed the diet containing 0.4% betaine than in the control group (p < .05).…”
supporting
confidence: 48%
“…Betaine as a common feed supplement has been widely used to enhance growth performance in fish. However, controversial results have been reported in different fishes, indicating a species‐specific betaine effect (Normandes et al., ). In this study, significantly higher FBW and SGR were observed in allogynogenetic gibel carp fed the diet containing 0.4% betaine than in the control group ( p < .05).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher growth performance was found with the supplementation of Bet in Indian major carp Labeo rohita (Shankar, Murthy, Pavadi, & Thanuja, ), pike perch Sander lucioperca fingerlings (Rahimabadi, Akbari, Arshadi, & Effatpanah, ), tilapia (Luo et al., ) and rainbow trout (Tiril, Alagil, Yagci, & Aral, ). To the contrary, Normandes, Barreto, Carvalho, and Delicio () concluded that Bet had no enhancing effect on growth of piauçu Leporinus macrocephalus . The possible reason for the positive effect of Bet on growth in the present study might due to the higher digestive enzyme activities (seen in Table ).…”
Section: Discussionmentioning
confidence: 99%
“…At the end of the experimental assay, the level of red beet and betaine separately, produced a significant decrease on Wf, SGR AND TGC, whereas fish fed with diet with 28% red beet and 0.9% betaine significantly reduced those parameters compared to the other dietary treatments. Betaine has been reported as a feeding stimulant to fish, inducing an increase of FI, and consequently, improving growth rate (Normandes et al 2006, Tiril et al 2008. However, in this study, the inclusion of betaine on rainbow trout diets did not show significant differences on FI and did not improve rainbow trout growth.…”
Section: : Discussionmentioning
confidence: 99%